(untitled) (Journal of Environmental Bioremediation and Toxicology, 2020)
Impact of indiscriminate discharge of abattoir wastewater has been a major cause of concern globally due to its negative effect on public and environmental health. Lack of wastewater treatment plants and guidelines for proper disposal in many developing countries generates other numerous ecological problems to the affected countries. Its role as a nutrient-provider for pathogenic microorganisms was highlighted by many researchers. Treatment of abattoir wastewater remains the main reliable and efficient means of reducing environmental pollution it may consequently cause. Environmental pollutants released through wastewater by abattoirs may be complicated due changes brought about by additional substance used during animal processing. Several methods adopted by abattoirs were reported to be effective. However, the need for improvement in line with environmentally friendly guidelines is recommended